Towards creep property improvement of selective laser melted Ni-based superalloy IN738LC. (10th June 2022) - Song, H.Y.; Lam, M.C.; Chen, Y.; Wu, S.; Hodgson, P.D.; Wu, X.H.; Zhu, Y.M.; Huang, A.J.
Highlights: SLM IN738LC superalloy was treated with unconventional two-step heating schemes. The 950 °C first step was found the most effective in redistributing the carbides. Carbide redistribution significantly reduced grain boundary pinning and promoted grain growth. Larger grain size led to 56% to 339% increments in creep life depending on creep strength. Abstract: Nickel-based superalloy IN738LC produced by selective laser melting (SLM) exhibits inferior high-temperature creep properties than its cast counterparts due to relatively smaller grain size, particularly for the plane normal to the building direction. This work studied effects of post heating strategy on the microstructure and especially the grain size to improve the high temperature creep resistance. The as-built microstructure exhibited a fine grain size and large quantities of M C carbides that could effectively hinder grain growth. It was found that unconventional two-step heat treatments could lead to substantial grain growth, and the effect is particularly prominent at a specific temperature. The ease of grain growth was explained after classifying the microstructural evolution (boundary carbide transformation) during each heating step and related to the reduced grain boundary pinning force from M C carbides. Creep tests validated the effect of the new heat treatment scheme on the SLM-processed IN738LC at 850 °C. An extended creep fracture life (1.5 to 4 times improvement) and lower secondary creep rates were achieved with samples subjected to the newly optimized two-step heat treatment. The complete creep curves are also firstly presented for SLM-IN738LC, confirming the effectiveness of grain growth and highlighting the importance of dedicated heat treatment for SLM superalloys.